SAPAAN KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA BIAK (SUATU ANALISIS KONTRASTIF) - TATUTA, SYANNE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research is an attempt to describe and analyze the term of address in English and Biak Language. In this research the writer uses Wardhaugh‟s, ErvinTripp‟s theories and Lado‟s concept, whereas the concepts relating to the terms of address to find out the differences of both languages. The aims of this research are to identify and classify and to find out the kinds of the term of address in English and Biak language and to contrast them, in order to find the differences. The English data were collected from several relevant text books and some sources from internet and previous thesis about the term of address that has been done before, whereas the Biak language data were collected from informants through investigation. The results show the types of English terms of address have (1) situations marked by status, (2) power, (3) identity and (4) generation, whereas Biak terms of address have (1) addressing terms using name (2) addressing terms using kinship, (3) addressing terms using intimacy, (4) addressing terms using respect and (5) addressing terms using mockeries. Keywords : Terms of address, English and Biak Language, Contrastive Analysis